2015
DOI: 10.1111/all.12692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of celiac disease in patients with severe food allergy

Abstract: The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
4
17
1
1
Order By: Relevance
“…It also underlines a common predisposition to develop autoimmune disease, as showed by the fact that about 10% of patients with positive tTGIgA in our study had either type 1 diabetes or an autoimmune thyroiditis. On the contrary, our study does not support the hypothesis of a link between atopy and CD, in agreement with previous studies [34, 35], nor of a link between food allergy and CD, as reported in recent studies [36]. …”
Section: Discussionsupporting
confidence: 74%
“…It also underlines a common predisposition to develop autoimmune disease, as showed by the fact that about 10% of patients with positive tTGIgA in our study had either type 1 diabetes or an autoimmune thyroiditis. On the contrary, our study does not support the hypothesis of a link between atopy and CD, in agreement with previous studies [34, 35], nor of a link between food allergy and CD, as reported in recent studies [36]. …”
Section: Discussionsupporting
confidence: 74%
“…The term gluten sensitivity may imply hypersensitivity or allergy . Actually, CD was found to be 5‐fold higher in patients with severe food allergy . However, we could not find an evidence to support a type I hypersensitivity in CD .…”
Section: Celiac Diseasecontrasting
confidence: 58%
“…Recent studies showed potential associations between atopic conditions and the risk of CD, 39,40,43 but the results have been inconsistent. For example, Pillon et al 44 reported that food allergy was associated with CD in 5% of children who had severe food allergy and 0.8% of children with mild food allergy. Another study, based on a large national data set that uses ICD codes, found a potential association between asthma and the risk of CD.…”
Section: Discussionmentioning
confidence: 99%